High-Pressure Processing of Kale: Effects on the Extractability, In Vitro Bioaccessibility of Carotenoids & Vitamin E and the Lipophilic Antioxidant Capacity - Mario Schmidt; Sofia Hopfhauer; Uwe Schwarzenbolz; Volker Böhm (MDPI AG, 2021)
High pressure processing (HPP) represents a non-thermal preservation technique for the gentle treatment of food products. Information about the impact of HPP on lipophilic food ingredients (e.g., carotenoids, vitamin E) is still limited in more complex matrices such as kale. Both the variation of pressure levels (200-600 MPa) and different holding times (5-40 min) served as HPP parameters. Whereas a slightly decreasing solvent extractability mostly correlated with increasing pressure regimes; the extension of holding times resulted in elevated extract concentrations, particularly at high-pressures up to 600 MPa. Surprisingly, slightly increasing bioaccessibility correlated with both elevated pressures and extended holding times, indicating matrix-dependent processes during in vitro digestion, compared to results of extractability. Moreover, the verification of syringe filters for digest filtration resulted in the highest relative recoveries using cellulose acetate and polyvinylidene difluoride membranes. The α-tocopherol equivalent antioxidant capacity (αTEAC) and oxygen radical antioxidant capacity (ORAC) assays of treated kale samples, chopped larger in size, showed increased antioxidant capacities, regarding elevated pressures and extended holding times. Consequently, one may conclude that HPP was confirmed as a gentle treatment technique for lipophilic micronutrients in kale. Nevertheless, it was indicated that sample pre-treatments could affect HP-related processes in food matrices prior to and possibly after HPP.